2004
DOI: 10.2298/hel0440211k
|View full text |Cite
|
Sign up to set email alerts
|

Determining new broomrape-infested areas, resistant lines and hybrids in Trakya region of Turkey

Abstract: New broomrape races have spread quickly year after year to reach 70% of the sunflower acreage in Trakya region of Turkey. These new races were more virulent in Turkey than in other countries such as Spain and at least one more race other than F race was observed in Trakya. Some inbred lines from Trakya Agricultural Research Institute-Edirne (TARI) exhibited resistance in some parts of the region, but the sunflower hybrid PR-64-A-95 exhibited resistance in all locations. This hybrid and other resistant lines wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 7 publications
2
20
0
1
Order By: Relevance
“…Recently, and as previously mentioned, populations overcoming race F resistance, named as races G and H, have also been identified in several countries and a continuous search for sources of resistance for these new races has been carried out (Kaya et al, 2004Pacureanu-Joita et al, 2009;Antonova et al, 2013). The non-existence of differential lines for new broomrape races makes defining broomrape races on the global level more difficult (Škorić et al, 2010).…”
Section: Breeding For Resistance To O Cumana Of Virulence Higher Than Fmentioning
confidence: 98%
See 2 more Smart Citations
“…Recently, and as previously mentioned, populations overcoming race F resistance, named as races G and H, have also been identified in several countries and a continuous search for sources of resistance for these new races has been carried out (Kaya et al, 2004Pacureanu-Joita et al, 2009;Antonova et al, 2013). The non-existence of differential lines for new broomrape races makes defining broomrape races on the global level more difficult (Škorić et al, 2010).…”
Section: Breeding For Resistance To O Cumana Of Virulence Higher Than Fmentioning
confidence: 98%
“…Turkey is another country where infections of sunflowers by O. cumana endanger the crop production in every growing season. Race F is widely distributed in Trakya region (Kaya et al, 2004), which accounts for more than half of the total area of sunflowers in the country. Also, race G has been identified in several locations of this same region .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance to this new race was found in germplasm of both cultivated and wild sunflowers (Sukno et al, 1999;Fernández-Martínez et al, 2000;Rodríguez-Ojeda et al, 2001), but a more virulent race G was identified soon after cultivars resistant to race F entered the market (Molinero-Ruiz and MeleroVara, 2005). Virulent races overcoming the resistance gene Or 5 have also been identified in Romania (Pâcureanu et al, 2004), Russia (Goncharov et al, 2004), Israel (Eizenberg et al, 2004), Bulgaria (Shindrova, 2006) and Turkey (Kaya et al, 2004). In the last country, the new races seem to be more virulent than those present in other countries.…”
Section: Introductionmentioning
confidence: 94%
“…Plants with attack frequency 0%À5% are considered resistant (R); with F D 5%À20% were accepted to be tolerant (T); 20%À50% À susceptible (S) and these with frequency higher than 50% highly susceptible (SS). [15] RNA extraction and cDNA synthesis…”
Section: Evaluation Of Infectionmentioning
confidence: 99%